Modelling Knowledge Synergy Evaluation - Ilona Skačkauskienė; Eglė Kazlauskienė; Aušra Katinienė (Montenegrin Journal of Economics)
Although nowadays knowledge is considered one of the main resources in organisations to create competitive advantage, there is a lack of research dedicated to the subject of knowledge and in particular knowledge synergy. After examining the content, types and properties of knowledge, the article provides definitions of knowledge potential and knowledge synergy that lead to the identification of its links and the constructive development of systematic research of knowledge synergy. The analysis of a knowledge synergy structure and the refinement of its components, i.e. employee’s knowledge, relations among employees and types of knowledge synergy relations, serve as a basis for a fundamental diagram of knowledge synergy evaluation and a calculation formula for knowledge synergy, as well as for suggestions on the evaluation of knowledge synergy components.